2020
DOI: 10.1093/jrs/feaa020
|View full text |Cite
|
Sign up to set email alerts
|

Acculturation of Syrian Refugees in the Netherlands: Religion as Social Identity and Boundary Marker

Abstract: We studied the acculturation processes of Syrian refugees in the Netherlands, based on semi-structured in-depth interviews. The study aims to investigate how Syrian refugees perceive the cultural distance caused by the differences and boundaries between Syrian and Dutch culture; how they cope with the boundaries and prejudice that they perceive; and which acculturation orientations they prefer. The research builds mainly on the framework of Berry’s acculturation model. Religion emerges as a prominent issue in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 39 publications
1
13
0
Order By: Relevance
“…Particularly for male participants in this study, Germany provided a novel landscape for the exploration and interpretation of varying faith practices outside of own's own, and the integration process often involved a determination of which practices were helpful, or not so helpful, to their mental health and well-being. These trends are similar to findings from a recent study of Syrian refugees in the Netherlands, which demonstrated that levels of commitment to faith or religious practices influence coping strategies and overall feelings of integration (30). Those demonstrating a stronger commitment to faith were more likely to utilize faith-based coping strategies when seeking mental health services, including seeking support from religious leaders or local religious institutions.…”
Section: Discussionsupporting
confidence: 85%
“…Particularly for male participants in this study, Germany provided a novel landscape for the exploration and interpretation of varying faith practices outside of own's own, and the integration process often involved a determination of which practices were helpful, or not so helpful, to their mental health and well-being. These trends are similar to findings from a recent study of Syrian refugees in the Netherlands, which demonstrated that levels of commitment to faith or religious practices influence coping strategies and overall feelings of integration (30). Those demonstrating a stronger commitment to faith were more likely to utilize faith-based coping strategies when seeking mental health services, including seeking support from religious leaders or local religious institutions.…”
Section: Discussionsupporting
confidence: 85%
“…Items from ‘Spiritual Change’ and ‘Personal Strength’ overlapped, loading onto the same factor. Speculatively, this may be related to the major role that religion plays in finding strength to overcome difficulties in resettled Syrians; qualitative studies have indicated that Islamic faith has been a source of empowerment and coping ( Hasan et al., 2018 ; Şafak-AyvazoĞlu et al., 2020 ). Previous studies have also found that the PTGI is best represented by fewer than five factors, though methodologically this may be explained by high correlations among factors or the small number of items within certain subscales ( Cobb et al., 2006 ; Taku et al., 2008 ; Kira et al., 2012 ).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, Syrian individuals resettling in the Netherlands may have difficulties navigating between the Syrian and Dutch cultural contexts. Specifically, these cultural contexts differ in the domains of social life, religion, gender roles, romantic relationships, and personal characteristics, which may contribute to Syrian people in the Netherlands perceiving a large cultural distance (Safak-Ayvazoglu et al, 2021). Despite seemingly large cultural differences, research indicates that Syrian people resettling in the Netherlands desire to engage with Dutch society, and this may be related to Syrian culture placing importance on collective community bonds (Safak-Ayvazoglu et al, 2021).…”
mentioning
confidence: 99%